Contemporary Criminology and Criminal Justice Theory - Skoll, G. author. aut Link
VII, 230 p.
Keywords: This book casts a critical eye on scholarship in the field of criminal justice, and offers some new orientations to help develop explanations for twenty-first century criminology and criminal justice studies.